The Influence of Sports Dance on the Physical and Mental Development of Contemporary College Students Based on Health Detection - Huali Huang (Emergency Medicine International)
The healthy growth of college students is related to the future development of the country and the prosperity of the nation. Under fierce social competition, college students are faced with academic pressure and employment pressure, resulting in the failure to improve their physical and mental health and their low self-acceptance level. Faced with such a situation, it is an important subject to solve the problem of the physical and mental health development of contemporary college students. As a sport that integrates sports and art, sports dance is worthy of in-depth discussion on the physical and mental development of college students. To analyze the impact of sports dance on the physical and mental development of contemporary college students, this paper uses an intelligent health monitoring system to monitor the health status of college students before and after physical dance exercise. It analyzes the influence of sports dance on the physical and mental development of college students from the aspects of cardiorespiratory endurance, muscular endurance, flexibility, and happiness. Finally, the results are obtained by conducting experiments with 10 college students. The experimental results show that the psychological well-being of college students who take physical dance exercise increases by 7.8%. Cardiorespiratory endurance and flexibility are both improved accordingly. Physical dance exercise promotes the physical and mental development of contemporary college students.